Tramadol toxicity-induced rhabdomyolysis - Khan, FahmiYousef; Yousef, Hind; Errayes, Mehdi (Journal of emergencies, trauma and shock, 2010)
Laboratory investigations on admission revealed creatinine kinase (CK) of 19,926 U/L, aspartate aminotransferase 680 U/L, alanine aminotransferase 229 U/L, blood urea nitrogen 10.1 mmol/L, serum creatinine 375 Î¼mol/L and serum myoglobin of 3,508 ng/ml. [...] rhabdomyolysis is a rare but serious complication of tramadol toxicity that requires a high index of suspicion as the clinical manifestations are non-specific; therefore, physicians should be aware of this complication because any delay in the diagnosis and treatment may lead to renal failure and other life-threatening rhabdomyolysis-related complications.